Natural products targeting the immune-metabolic regulatory network in pulmonary hypertension: mechanisms, classification, and therapeutic prospects - Ma, Jianli; Cao, Xiyu; Yang, Xiuli; Zhu, Yi; Wang, Hualing; Liu, Yundou; Chen, Ke; Liu, Xiao; Zhang, Chuantao (Frontiers in Pharmacology, 2026)
Pulmonary hypertension (PH) is a clinical syndrome characterized by progressive elevation of pulmonary vascular resistance, whose pathological process is closely related to the crosstalk between immune dysregulation and metabolic remodeling, forming a complex immune-metabolic regulatory network. The abnormal activation and polarization of innate immune cells, as well as the imbalance and autoreactivity of the adaptive immune system, jointly drive the pulmonary vascular inflammatory response. Metabolic reprogramming of pulmonary artery smooth muscle cells, pulmonary artery endothelial cells, and others provides the energy and material basis for abnormal proliferation of vascular cells. Abnormal products generated by metabolic disorders can regulate energy metabolism of immune cells and inflammatory signals; abnormal activation of immune signals can remodel metabolic pathways. The two interact through mechanisms such as the mitochondria-inflammasome axis and epigenetic regulation, collectively promoting vascular remodeling. Targeting this network, natural products exhibit unique advantages due to their characteristics of multiple components and multiple targets. Among them, immunomodulatory natural products can improve the immune microenvironment by inhibiting core inflammatory pathways and regulating immune cell infiltration. Metabolic regulatory natural products focus on restoring mitochondrial function and correcting abnormal glucose and lipid metabolism to interfere with metabolic remodeling. By targeting mTOR, SIRT1 and other pivotal molecules, immune metabolic dual regulatory natural products can synchronously regulate immune response and metabolic activities, and block the vicious cycle of immune activation, metabolic disorder and vascular remodeling. However, challenges remain, including insufficient mechanistic depth and a significant gap between preclinical models and clinical application. Further research into these mechanisms may provide novel insights for PH therapy and improve patient prognosis.